Taxonomy of the super-cryptic Hyperolius nasutus group of long reed frogs of Africa (Anura: Hyperoliidae), with descriptions of six new species - Channing, A.; Hillers, A.; Lötters, S.; Rödel, M.-O.; Schick, S.; Conradie, W.; Rödder, D.; Mercurio, V.; Wagner, P.; Dehling, J.m.; du Preez, L. H.; Kielgast, J.; et al. (Zootaxa, 2013)
Specimens from across the range of the Hyperolius nasutus species group were sequenced for two mitochondrial genes and one nuclear gene. Advertisement calls were recorded from the same specimens where possible, and morphological characters were compared. Bayesian inference and maximum likelihood produced a tree indicating 16 clades. The clades show little or no overlap in combinations of 16S sequence difference, shared tyr haplotypes, advertisement call parameters, snout profiles and webbing. On the basis of these data we recognise H. acuticeps, H. adspersus, H. benguellensis, H. dartevellei, H. igbettensis, H. nasutus, H. nasicus, H. poweri, H. viridis and describe six new species: Hyperolius friedemanni sp. nov. Mercurio & Rödel, Hyperolius howelli sp. nov. Du Preez & Channing, Hyperolius inyangae sp. nov. Channing, Hyperolious jacobseni sp. nov. Channing, Hyperolius rwandae sp. nov. Dehling, Sinsch, Rödel & Channing, and Hyperolius lupiroensis sp. nov. Channing. Hyperolius lamottei is confirmed to be outside the H. nasutus group clade. Hyperolius granulatus, H. oxyrhynchus, H. punctulatus and H. sagitta are assigned as junior synonyms. As our results are based on a small number of specimens, these hypotheses await testing with larger sample sizes and more characters. A species distribution model suggests where outlier populations might be found.